COMPARISON ANALYSIS OF INCOME ON ORGANIC VEGETABLE AND INORGANIC VEGETABLES IN AMBON ISLAND - Ester Dorina Leatemia; Johanna M Luhukay (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2022)
Increasing agricultural production by using chemical fertilizers and pesticides continuously and exceeding the threshold for use will cause new problems for health and the surrounding environment. Organic vegetable farming has been started because people are becoming aware of the dangers of using chemical pesticides. This study aims to describe the characteristics of organic and inorganic vegetable farming, describe the marketing of organic and inorganic vegetables and analyze the comparison of organic and inorganic vegetable farming income on Ambon Island. The method used in sampling is the census method. The results showed that implementation of organic and inorganic vegetable farming in Telaga Kodok Hamlet and Waiheru Village there were differences in vegetable cultivation both in land preparation and processing, seeding, fertilization, and controlling plant pest organisms (OPT). Most farmers (80%) sell organic vegetables to distributors (modern retail markets) when compared to selling vegetables to consumers (20%). The reason farmers sell organic vegetables to distributors (modern retail markets) is they are partners. Farmers in Waiheru Village sell their inorganic vegetable products to retailers (73.32%) when compared to being sold to collectors (13.34 percent) and sold directly to consumers (13.34 percent). The income of organic vegetable farmers is higher (Rp. 2,338,580.29) when compared to the income of inorganic vegetable farmers (Rp. 1,292,187.84). This is due to the difference in the selling price of organic vegetables and inorganic vegetables, and the production costs incurred by organic vegetable farmers are smaller than those of inorganic vegetable farmers. Keywords: income, marketing, organic vegetables, inorganic vegetables